Wind effect on bottom shear stress, erosion and redeposition on Zostera noltei restoration in a coastal lagoon; part 2. (5th January 2019) - Alekseenko, E.; Roux, B.
Abstract: This paper concerns wind effect on bottom shear stress ( B S S ), resuspension and redeposition of bottom sediments in the nearshore areas of the Etang de Berre (EB), a semi-enclosed lagoon, in the context of Zostera noltei (Z.n.) restoration. As in our previous paper, the first step is to compare B S S with its threshold, B S S c r, for a wind speed of 21 m/s. But, here, a new simulation is performed for 16 wind directions regularly spaced. It permits to analyze the combined effect, over one year, of these winds on the erosion risk. For that, a mean value of | B S S |, i.e., a weighted average based on the frequency of each wind directions, has been determined and compared to B S S c r for a class of roughness parameters. A similar averaging of B S S → has been also evaluated to obtain the direction of an average bottom current. Then, the most important contribution of the present paper concerns the modelling of the wind-induced sediment erosion, transport and redeposition. The specific module SEDIM/MARS3D is used to determine how the thickness of a given mud-sand sedimentary layer can be changed by the wind-induced current during typical periods of 3 days of constant wind. This numerical study is performed for three wind speeds in the two main wind directions: N-NW and S-SE. The time evolution of this initial sedimentary layer permits to determine where and when the erosion would be large enough to be a stressor for the Z.n. restoration. For an extreme erosion rate of 10 − 3 kg/m 2 /s, for a strong wind speed of 21 m/s and an initial sedimentary layer of 15 cm, all this layer would be eroded in several nearshore areas after 3 days. The erosion risk is maximum along the eastern shore, where an additive effect of the two opposite winds can be expected. Indeed, S-SE and N-NW winds create coastal jets of opposite direction and of about the same intensity exerting alongshore erosion and deposition at about the same places. The present results concerning the time evolution of erosion depth induced by the wind improve our knowledge of the erosion risk on the Z.n. restoration in EB. They will be useful to appropriately orient the action of politics and managers for a future restoration program. Highlights: Bottom shear stress in a windy semi-enclosed lagoon. Wind impact on the time-evolution of the thickness of an erodible bottom sediment. Identification of burial or erosion places vs future replanting program.